Starting out right a guide to promoting children's reading success - Burns, Marie Susan; Griffin, Peg; Snow, Catherine E. (National Academy Press, 1999)
"Presents practical guidelines, program descriptions, advice on resources, and strategies that can be used by parents and caregivers to provide children, from birth through the first years of formal training, with a solid basis upon which to build reading skills."